Lügenpresse: The lying press and German journalists' responses to a stigma. (November 2021) - Koliska, Michael; Assmann, Karin
The term Lügenpresse, 'lying press', was used by the German National Socialist Party before and during the Third Reich to discredit the news media and to undermine public trust. By 2014, reports of verbal and physical attacks on journalists and news organizations by individuals calling them Lügenpresse, had again become a frequent feature of the public discourse in Germany. While the term 'fake news' is used to similar effect and intent in the United States, Lügenpresse is a historically and politically charged expression of distrust in news media on an institutional level. This research examines the responses and institutional strategies of 27 news editors and executive editors in Germany's leading broadcast, print and online news organizations to the accusations that they are lying to their audiences. Findings indicate that the reemergence of the term Lügenpresse, has led to considerable self-reflection within institutions, in an effort to counter the lack of trust and to demonstratively better serve the public. The main focus across newsrooms is on improving established processes and on making professional standards and practices more visible to the audience.